Pricing nature cost-benefit analysis and environmental policy - Hanley, Nick. (Cheltenham Edward Elgar, 2009)
Cost-Benefit Analysis (CBA) is one of the most useful tools of applied economics for the social appraisal of public projects and government policies. Nick Hanley and Edward Barbier show how CBA can be applied to environmental policy choice and environmental resource management. They cover the conceptual underpinnings of CBA, practical methods for applying CBA, and a wide range of case study applications from Europe, North America and developing countries. Issues such as the value of ecosystem services and the special problems posed for CBA by environmental management are brought into close focus.
Includes bibliographical references and index.
Keywords: Environmental policy -Cost effectiveness